Pain Perception Modulates Synaptic and Somatic Plasticity in the Dentate Gyrus of Rats - Arslan Soley; Tufan Esra; Balkaya Hacer; Günaydın Türker Buse; Melike Durukan Sebahat; Çimen Ayşenur; Süer Cem (International Journal of Pain Management, 2024)
An experimental study examines how pain perception alters synaptic and somatic plasticity in the dentate gyrus. It summarizes methods, key electrophysiological findings, and implications for pain‑related cognitive effects.
Keywords: Dentin Erosion